AC-X: Characteristic Antinuclear Antibody Patterns of Two Anti-Mi-2 Autoantibody-Positive Dermatomyositis Patients—A Case Report - Wu, Ziyan; Xu, Honglin; Zhang, Shulan (Frontiers in Immunology, 2022)
Here we reported two anti-Mi-2 autoantibody positive dermatomyositis (DM) patients with characteristic antinuclear antibody(ANA)immunofluorescence pattern. Autoantibodeswerescreenedby indirect immunofluorescence (IIF)onHEp-2 cells(Euroimmune, Germany)andconfirmed by line immunoblot (ANA Profile 3 - Euroimmune, Germany). These two patients were positive for ANA(speckled, titer 1:320)，followed by confirmation of positiveanti-Mi-2α and anti-Mi-2β positive and negative for all other antibodies. We found characteristic ANA pattern of anti-Mi-2 antibody that differed from the AC-4 pattern ,especially in the morphology of mitotic cells (metaphase, anaphase, and telophase). Thus, we would like to suggest reporting this characteristic antinuclear antibody patterns as a new AC type, as AC-X.